Multi‐ethnic comparisons of diabetes in heart failure with reduced ejection fraction: insights from the HF‐ACTION trial and the ASIAN‐HF registry. (26th June 2018) - Cooper, Lauren B.; Yap, Jonathan; Tay, Wan Ting; Teng, Tiew‐Hwa K.; MacDonald, Michael; Anand, Inder S.; Sharma, Abhinav; O'Connor, Christopher M.; Kraus, William E.; Mentz, Robert J.; Lam, Carolyn S.; ,
Abstract : Aim: To describe differences in patient characteristics and outcomes by ethnicity in patients with diabetes mellitus (DM) and heart failure (HF) with reduced ejection fraction (HFrEF, ejection fraction ≤35%) in a multi‐ethnic cohort. Methods and results: Patient level data from two cohorts (HF‐ACTION and ASIAN‐HF) were combined, and patients grouped by self‐reported ethnicity. DM was defined as the presence of a clinical diagnosis and/or receiving anti‐diabetic therapy. A total of 6214 (1324 whites, 674 blacks, 1297 Chinese, 1510 Indians, 717 Malays, 692 Japanese/Koreans) patients were included. The overall prevalence of DM was 39.5% ( n = 2454). The prevalence of DM was lowest in whites (29.3%), followed by Japanese/Koreans (34.1%), blacks (35.9%), Chinese (42.3%), Indians (44.2%), and highest in Malays (51.9%). The correlation between age, sex, body mass index, coronary artery disease, hypertension, atrial fibrillation, peripheral vascular disease and chronic kidney disease with DM differed significantly by ethnicity ( P for interaction <0.05). The strongest correlations were seen in Malay women, whites with obesity, Indians with coronary artery disease and hypertension, and blacks with chronic kidney disease. On multivariable analyses, DM was significantly associated with the composite of 1‐year overall mortality/HF hospitalization (hazard ratio 1.37, 95% confidence interval 1.19–1.57; P < 0.001), with no interaction by ethnicity ( P for interaction =0.31). Conclusions: There is marked heterogeneity in the prevalence and correlates of DM among different ethnic groups with HF worldwide. Subgroups particularly predisposed to DM warrant special attention, since DM increases the combined risk of morbidity and mortality in all ethnicities with HF.